Synthesizing Islamic Values-Based Environmental Education as a Conceptual Framework for Ethics and Pedagogy: A Systematic Literature Review - Moh Subhan; Agus Sholahuddin; Shonhadji Shonhadji (TA`DIBUNA, 2026)
This research aims to formulate a conceptual framework for value-based Islamic environmental education using the method of systematic literature review. This research identifies Islamic values such as tawhid, khalifah, amanah, mīzān, rahmah, and isrāf as the ethical and spiritual foundation of environmental education. The findings indicate that most of the literature still places these values within a normative-theological context without developing practical pedagogical designs. An experiential learning approach and natural spaces that align with the principles of Islamic spirituality, but have not been widely and systematically implemented in education. This research also highlights the importance of intersectional dimensions such as gender, child agency, and social justice in Islamic environmental education, which have received less attention in the literature to date. In conclusion, this research confirms the importance of reformulating Islamic-based environmental education to make it more contextual, spiritual, and inclusive. This research contributes theoretically to the development of Islamic education and ecopedagogy, as well as opening new directions for future applied research.